Not all deviance is criminal: deviance in everyday life and the development of a non-criminal deviance scale - Mowen, Thomas J. (Deviant behavior, 2023)
The field of deviance generally encompasses two major forms of deviant behavior: Formal and informal deviance. Formal deviance refers to acts that violate a law, while informal deviance refers to acts that violate a social norm. Yet, as a total proportion of deviance in a given society, formal deviance - crime - is rare. While the focus on crime is warranted, it has resulted in far less quantitative assessment and understanding of informal deviance. The goal of this study is to develop and test a quantitative scale called the non-criminal deviance scale (NCDS). Drawing from expert evaluations, we create a 13-item NCDS, then test it against theoretically informed covariates using a sample of 780 young adults. Findings reveal key constructs (e.g. self-control, age) influence variations in the NCDS. Results demonstrate that much like scales used in crime research, non-criminal deviance can also be captured quantitatively via a scale. Given the relatively common nature of informal deviance - particularly compared to formal deviance - this is a crucial first step in understanding general patterns in non-criminal deviant behaviors.